NATIVE AMERICAN SPIRITUALITY AND NATURAL LANDSCAPE IN N. SCOTT MOMADAY'S POETRY - Jasim, Mustafa Amjed; Kamal Addin, Soukaina Hameed (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Native Americans are the first people to reside in the United States of America, specifically the northern part of it. One of the famous Native American poets is Scott Momaday. Momaday is a Kiowa Native American poet, storywriter, and novelist. The purpose of this research is to explain traditions, and the significance of natural landscape in Scott Momaday's poetry, focused on words, images and metaphors by means of descriptive qualitative method.  The researchers endeavor to apply a concept of Shamanism in Momaday's poetry. Shamanism is an ancient healing tradition, and a way of life. It is a way to connect with nature and all the creations. Every plant for native Americans symbolizes a certain thing, cherries symbolize mercy, and they can heal wounds by the ointment. The data are taken from  the poems related to nature and tradition as in The Earth, Eagle Feather Fan, The Delight Song of Tsoai-Talee, and Angle of Geese.  The results show that natural landscape and traditions are linked to spirituality. For Native Americans, there is no difference between animate and inanimate objects;   everything in this life has a soul.